A 5-year single-center experience in heart transplantation in Rostov oblast - V. L. Korobka; M. Yu. Kostrykin; A. A. Duzhikov; V. D. Shamkhanyants; D. K. Lobachev; O. V. Kotov; A. A. Kartashov; A. V. Sumin; M. V. Gusnay; A. I. Trapeznikova; E. A. Kudryashova; R. V. Korobka (Вестник трансплантологии и искусственных органов, 2024)
Objective: to evaluate the outcomes of heart transplants performed at Rostov Regional Clinical Hospital within five years.Materials and methods. Between 2017 and 2022, 29 orthotopic heart transplants (HT) were performed in our clinic. Heart failure was caused by postinfarction cardiosclerosis (21 cases, 72.4%) and dilated cardiomyopathy (8 cases, 27.6%). Among the recipients, 27 (93.1%) were men and 2 (6.9%) were women. Mean age was 53.14 ± 8.7 years (34 to 67 years). All patients received quadruple-drug immunosuppressive therapy, including induction with monoclonal antibodies; calcineurin inhibitor, mycophenolic acid, and corticosteroid were used after HT.Results. In-hospital mortality was 10.34% (n = 3). The causes of death were multiple organ failure and infectious and septic complications. After discharge, 4 (13.8%) recipients died over 5 years. Rejection reaction with the development of graft dysfunction (3 recipients, 75%), infectious and septic complications (1 recipient, 25%) were the causes of death in the long-term period. The survival rate was analyzed according to the Kaplan–Meier estimate. One-year survival was 80.9%. Three-year survival rate corresponded to the 5-year survival rate – 70.56%. Five-year survival of patients surviving the first year after HT was 86.1%. Maximum follow-up period was 64 months.Conclusion. HT continues to be the gold standard for patients with end-stage heart failure. Five-year HT experience in our center has shown a survival rate that is comparable to that of the International Society for Heart and Lung Transplantation (ISHLT).